2019
DOI: 10.1186/s13046-018-1019-5
|View full text |Cite
|
Sign up to set email alerts
|

JAK/Stat5-mediated subtype-specific lymphocyte antigen 6 complex, locus G6D (LY6G6D) expression drives mismatch repair proficient colorectal cancer

Abstract: BackgroundHuman microsatellite-stable (MSS) colorectal cancers (CRCs) are immunologically “cold” tumour subtypes characterized by reduced immune cytotoxicity. The molecular linkages between immune-resistance and human MSS CRC is not clear.MethodsWe used transcriptome profiling, in silico analysis, immunohistochemistry, western blot, RT-qPCR and immunofluorescence staining to characterize novel CRC immune biomarkers. The effects of selective antagonists were tested by in vitro assays of long term viability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…An increasing number of studies have suggested an interaction between immune response and pathophysiological processes [ 21 , 22 ]. Moreover, JAKs play a critical role in immune regulation by invoking intracellular signaling pathways in cancers [ 23 ]. Therefore, we next evaluated the correlation between JAK3/TYK2 and immune infiltration in STAD.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have suggested an interaction between immune response and pathophysiological processes [ 21 , 22 ]. Moreover, JAKs play a critical role in immune regulation by invoking intracellular signaling pathways in cancers [ 23 ]. Therefore, we next evaluated the correlation between JAK3/TYK2 and immune infiltration in STAD.…”
Section: Resultsmentioning
confidence: 99%
“…CRCs require interaction with many different host immune cell populations for their growth and survival, including regulatory T cells (Treg) and myeloid-derived suppressor cells (MDSC), mast cells, and tumor associated macrophages (TAM) [55]. Recent studies suggest that a substantial portion of the effects attributed to EGFR antagonist treatment may be based on indirect effects beyond cancer cells [40,41,42,55,56,57,58,59,60,61,62].…”
Section: Contribution Of Tumor Microenvironment To Acquired Resistmentioning
confidence: 99%
“…GSEA revealed that the ATG signature included genes that were robustly involved in multiple immune/ in ammatory pathways including IL6/JAK/STAT3, IL2/STAT5, IFN-α, IFN-γ, TNF-α/NF-κB, and the in ammatory response presented a particular relation to CRC proliferation or prognosis as previous studies revealed [21][22][23][24][25]. As our ndings suggested that a high autophagy risk score correlated with the downregulation of these immune/ in ammatory pathways, we speculated that autophagy might play a role in CRC tumorigenesis and tumor proliferation via an anti-immune/ anti-in ammatory response.…”
Section: Discussionmentioning
confidence: 82%